Digest: Pursue or ambush? Phenotypic disparity in the carnivore forelimb. (1st August 2018) - English, Holly M.
Abstract: The way an animal moves reveals key aspects of its ecology. Carnivore forelimbs are adapted to their predation style, and the structure of the elbow joint can indicate hunting strategy. In this issue, Figueirido (2018) investigates phenotypic disparity, or morphological variation, in domestic dog breeds, the canid family, and the carnivore order using the elbow joint as an indicator of movement and predatory behavior.